IInterpretasi Dan Makna Kritik Sosial Dalam “Komik Strip Untuk Umum (Kostum)” Periode 1 Desember – 31 Desember 2017 - Babus Salam; Iwan Joko Prasetyo; Daniel Susilo (Universitas Serang Raya, 2018)
Theres many ways can be done to appreciate the voices of messages and criticisms through creative ways, one of them through comics. One of the Indonesian comic artists who used comics as a medium of social criticism was Haryadhi through his